Description of five new species of the subgenus Tachycines (Gymnaeta) (Rhaphidophoridae: Aemodogryllinae: Aemodogryllini) from caves in Guizhou, China - Lin, Chun; Huang, Shihui; Luo, Changqing (Zootaxa, 2023)
The genus Tachycines contains two subgenera: T. (Tachycines) and T. (Gymnaeta), and the species of this genus occur mainly in Southeast and East Asia, including Myanmar, Philippines, Vietnam, India, and China. Many species of the subgenus Tachycines (Gymnaeta) are cavernicolous. In this study, five new cave species of this subgenus, namely Tachycines (Gymnaeta) lingulatus sp. nov., Tachycines (Gymnaeta) multispinus sp. nov., Tachycines (Gymnaeta) microtuberculatus sp. nov., Tachycines (Gymnaeta) ovalius sp. nov., and Tachycines (Gymnaeta) conicus sp. nov., from Guizhou Province, China are identified and described. Morphological information of males and females of the five new species are provided.